2006
DOI: 10.1111/j.1460-9568.2006.04688.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of auditory cortex lesions on the discrimination of frequency‐modulated tones in rats

Abstract: The lateralization of functions to individual hemispheres of the mammalian brain remains, with the exception of the human brain, unresolved. The aim of this work was to investigate the ability to discriminate between falling and rising frequency-modulated (FM) stimuli in rats with unilateral or bilateral lesions of the auditory cortex (AC). Using an avoidance conditioning procedure, thirsty rats were trained to drink in the presence of a rising FM tone and to stop drinking when a falling FM tone was presented.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
58
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(62 citation statements)
references
References 29 publications
3
58
0
Order By: Relevance
“…This AC asymmetry has recently been confirmed in rats (43). In human functional (f)MRI experiments, we found that the categorization of direction of FM stimuli produced dominant blood-oxygen leveldependent (BOLD) activation of right AC, but categorization of their duration resulted in activation of left AC (44).…”
mentioning
confidence: 70%
“…This AC asymmetry has recently been confirmed in rats (43). In human functional (f)MRI experiments, we found that the categorization of direction of FM stimuli produced dominant blood-oxygen leveldependent (BOLD) activation of right AC, but categorization of their duration resulted in activation of left AC (44).…”
mentioning
confidence: 70%
“…Behavioral studies in rodents (e.g., Wetzel et al, 1998;Rybalko et al, 2006) suggest an asymmetry in cortical processing, where the right hemisphere has dominance for discrimination of frequencymodulated tones. It is possible that our observations of 2-DG uptake in contralateral cortex are confounded by our manipulation of the left ear, such that if the right ear were manipulated, the results in left cortex may not be identical to our current findings.…”
Section: Cortical Reaction To Unilateral Hearing Lossmentioning
confidence: 99%
“…In fact, prior studies have pointed towards auditory cortex as critical for the discrimination of FM sweeps in many species including mice (Letzkus et al, 2011), rats (Rybalko et al, 2006), and Mongolian gerbils (Ohl et al, 1999). In bats, cortical circuits responsible for FM sweep processing, such as the FM-FM area involved in echolocation, have been implicated (Suga et al, 1983).…”
Section: Introductionmentioning
confidence: 99%